Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1111/bcp.13425
|View full text |Cite
|
Sign up to set email alerts
|

Drug–drug interaction potential in men treated with enzalutamide: Mind the gap

Abstract: AIMSMetastatic castration-resistant prostate cancer (mCRPC) patients are generally older patients with several co-morbidities and are therefore at increased risk of complications due to drug-drug interactions (DDIs). We assessed the prevalence of potential DDIs in a cohort of mCRPC patients treated with enzalutamide. METHODSWe conducted a retrospective review of pharmacy records to retrieve individual drug histories of mCRPC patients who started enzalutamide therapy in a tertiary care setting. Potential DDIs w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 29 publications
4
32
0
1
Order By: Relevance
“…The present analyses of the phase III ARAMIS trial demonstrated that almost all patients with nmCRPC receiving androgen-deprivation therapy with androgen receptor inhibitor therapy have comorbid conditions that require the use of concomitant medications. Individual patient data in ARAMIS indicated that many patients were receiving multiple comedications, as others have also reported [10]. As expected in this population (median age 74 years), the most common comorbidities included hypertension and other cardiovascular disorders, obesity, hyperlipidemia, osteoarthritis, and diabetes.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…The present analyses of the phase III ARAMIS trial demonstrated that almost all patients with nmCRPC receiving androgen-deprivation therapy with androgen receptor inhibitor therapy have comorbid conditions that require the use of concomitant medications. Individual patient data in ARAMIS indicated that many patients were receiving multiple comedications, as others have also reported [10]. As expected in this population (median age 74 years), the most common comorbidities included hypertension and other cardiovascular disorders, obesity, hyperlipidemia, osteoarthritis, and diabetes.…”
Section: Discussionsupporting
confidence: 63%
“…The potential for DDIs is an important consideration when selecting an androgen receptor-targeting therapy for patients with nmCRPC. Loss of efficacy with treatments for patients’ comorbidities or sustaining an increased risk of AEs are potential outcomes of DDIs [10, 24]. Extensive investigation in preclinical/phase I studies indicated that darolutamide has a favorable DDI profile.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, this case represents a further example of the lack of information on an important drug-drug interaction. Consistent with our recently published article in the journal, no uniform recommendation on the management was found for three widely used drug interaction databases (Micromedex®, Lexicomp®, and the drug Dutch database) [17].…”
Section: Figuresupporting
confidence: 70%
“…We did not obtain totality data such as herbal medicines, OTC drugs and vitamins taken by outpatients, which might contribute to the underestimation of pDDIs. Third, there are several available DDI databases with the disparities in the inclusion of pDDIs and the severity grading [28]. However, only one screening database was employed to estimate the prevalence of pDDIs.…”
Section: Potential Clinical Consequences and Mechanisms Of Pddismentioning
confidence: 99%